INTRODUCING ARTIFICIAL INTELLIGENCE INTO THE MANAGEMENT AND DISTRIBUTION OF ELECTRICITY GENERATED FROM RENEWABLE ENERGY SOURCES - Basim Jabbar Majeed (European Science Publishing, 2025)
The most important step in the modern era is the distribution and management of electricity using artificial intelligence, particularly energy generated from renewable energy sources. This ensures the sustainability of energy sources and thus improves the efficiency of electrical grids. There are many challenges facing the renewable energy sector, resulting from fluctuations in production, climate disturbances, and imbalances in supply and demand. Artificial intelligence can help solve these challenges. Using machine learning techniques, environmental forecasting, and efficient management of these resources can improve the accuracy of forecasting production levels from solar and wind energy. Smart grids are among the most prominent applications in this field because they represent a model for artificial intelligence applications, which rely on improving energy distribution among consumers based on their actual needs, thus increasing efficiency and reducing losses. It can also optimize storage systems by determining optimal charging and discharging times for stored energy, reducing the need for massive infrastructure investments. The need for advanced security solutions has emerged due to the presence of security threats related to cyberattacks on smart grids. However, related challenges include high investment costs and the need for accurate and reliable data from various operating environments. However, the future is moving toward integrating artificial intelligence into renewable energy management. This will be the ideal solution for addressing issues of improving energy production and storage, thereby enhancing grid efficiency and making them more flexible, meeting energy needs, and achieving global sustainability and clean energy goals.
Keywords: Artificial Intelligence, Renewable Energy, Energy Management, Energy Sustainability, Smart Grid Security.